2020
DOI: 10.1590/1806-9665-rbent-2019-47
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Bacillus thuringiensis strains to control Spodoptera eridania (Cramer) (Lepidoptera: Noctuidae) population

Abstract: The main objective of this study was to characterize the toxicity and genetic divergence of 18 Bacillus thuringiensis strains in the biological control of Spodoptera eridania. Bacterial suspensions were added to the S. eridania diet. Half of the selected B. thuringiensis strains caused high mortality seven days after infection. The genetic divergence of B. thuringiensis strains was assessed based on Enterobacterial Repetitive Intergenic Consensus (ERIC) and Repetitive Extragenic Palindromic (REP) sequences, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Several studies have reported that ERIC markers are more informative than REP markers in discriminating Bt strains 32,26,9,35 , as was also verified in this research, suggesting that ERIClike sequences may be more widely distributed than REP-like sequences in Bt 26 . Among all the markers, GTG 5 was not as effective in discriminating between isolates of BtMA, indicating low genetic diversity.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Several studies have reported that ERIC markers are more informative than REP markers in discriminating Bt strains 32,26,9,35 , as was also verified in this research, suggesting that ERIClike sequences may be more widely distributed than REP-like sequences in Bt 26 . Among all the markers, GTG 5 was not as effective in discriminating between isolates of BtMA, indicating low genetic diversity.…”
Section: Discussionsupporting
confidence: 84%
“…The repetitive element palindromic-polymerase chain reaction (rep-PCR) technique has been used to investigate the interspecific and intraspecific genetic diversity of Bt isolates, allowing us to correlate them with the geographic regions of collection, the origin of the substrate, morphological, biochemical and genetic characteristics, and rates of mortality and toxicity against insect pests and vectors 32,50,21,19,35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations